Peningkatan Keterampilan Praktik Shalat melalui Metode Demonstrasi pada Siswa Kelas III SD Negeri 24 Biaro - Rika Septiana Sari; Riska Jamanita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve students' prayer practice skills through the application of the demonstration method in learning Islamic Religious Education (PAI) in class III SD Negeri 24 Biaro. The background of this study is the low ability of students in practicing prayer, both in terms of reading and movement. The method used was Classroom Action Research (PTK) with the subject of 19 students. The research was conducted in several cycles consisting of planning, implementation, observation, and reflection stages. Data were obtained through observation sheets of teacher and student activities, as well as the results of prayer practice assessments which were analyzed using the percentage of learning completeness with a KKM of 75. The results showed an increase in prayer practice skills from cycle to cycle. In cycle I, students who were complete only reached 44% with most students still passive, less focused, and embarrassed to practice prayer movements. After improvements were made through the demonstration method in cycles II and III, the number of completed students increased significantly to reach more than 90%. Thus, it can be concluded that the demonstration method is effective in improving students' prayer practice skills, as well as making PAI learning more interactive, varied, and meaningful.